2003
DOI: 10.1063/1.1594817
|View full text |Cite
|
Sign up to set email alerts
|

Ga-doping effects on electrical and luminescent properties of ZnO:(La,Eu)OF red phosphor thin films

Abstract: Theoretical and experimental approach on dielectric properties of ZnO nanoparticles and polyurethane/ZnO nanocomposites J.Erratum: "Structural, electrical and optical properties of aluminum doped zinc oxide films prepared by rf magnetron sputtering" [J.Red thin-film phosphors were fabricated based on a ZnO:͑La,Eu͒OF nanocomposite structure where ͑La,Eu͒OF nanoparticles were dispersed in a ZnO film matrix. The films were deposited on glass substrates by a sol-gel method at a low temperature of 600°C using trifl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 35 publications
3
31
0
1
Order By: Relevance
“…We believe that the occupied sites of Eu 3+ ions in ZnO:Eu films are a little sensitive to the formation process of films. Compared with the previously reported sol-gel derivation of ZnO:Eu films [12][13][14][15][16], our experiment featured the addition of macromolecular organic solvent (DMF) and surfactant (PVP) in the precursor sol, which possibly affected the position of Eu 3+ ions in the formed gel and even in the consequently fired ZnO films. Obviously, in our further work, we should try to identify the exact positions of Eu 3+ ions in the ZnO films.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We believe that the occupied sites of Eu 3+ ions in ZnO:Eu films are a little sensitive to the formation process of films. Compared with the previously reported sol-gel derivation of ZnO:Eu films [12][13][14][15][16], our experiment featured the addition of macromolecular organic solvent (DMF) and surfactant (PVP) in the precursor sol, which possibly affected the position of Eu 3+ ions in the formed gel and even in the consequently fired ZnO films. Obviously, in our further work, we should try to identify the exact positions of Eu 3+ ions in the ZnO films.…”
Section: Resultsmentioning
confidence: 95%
“…Eu-doped semiconductors (such as ZnO and GaN) [3,4] and insulators (such as Al 2 O 3 , Y 2 O 3 and SiO 2 ) [5][6][7] have been applied in thin-film electroluminescent devices [8], optoelectronic or cathodoluminescent devices [9] and telecommunications and lasers [10]. The popular routes to preparing ZnO:Eu films mainly belong to the chemical solution deposition, for example, spray pyrolysis [11] and sol-gel process [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the ZnO:Eu 3+ samples doped with 1, 3, 5, 7 and 10 wt% are all alike: they present a green broad emission band from 400 nm to 600 nm centered about 516 nm, this band is due to the intrinsic defects emission of ZnO host. however, in addition to the broad band characteristic of defects in ZnO appear the photoluminescence spectra of the Eu 3+ doped powders: effectively, the sharp peaks in 579, 591, 613, 618, 650 and 770 nm are related to the direct intra-4f transitions in Eu , 1, 2, 3, 4), the most intense emission is associated to the 5 D 0 → 7 F 2 emission in the red spectral region (613 nm) and is due to an allowed electric-dipole transitions with inversion antisymmetry [19], which results in a large transition probability in the crystal field; in our case this emission is split in two components of 613 and 618 nm, theoretically, the 7 F 2 level gives three crystal field levels of A1 and 2E with 3C v symmetry, because A1 and one of two E levels have close energy levels, two emission peaks (A1 and E at 613 and 618 nm) can be overlapped in the PL spectra [34] [35]. The peak at 591 nm is due to the 5 where % is the Eu 3+ ions concentration, the solid curve in Figure 5 represents the fit to the experimental data, the integrated intensity increases as an exponential function as the doping concentration increase which indicates the enhanced energy transfer between the ZnO host and activator Eu 3+ ions.…”
Section: Xps Analysismentioning
confidence: 99%
“…The grain growth of ZnO is promoted by fast diffusion of Zn interstitials at higher temperatures [20]. In the case of trivalent cation doping, the concentration of the zinc interstitials is reduced for charge compensation, resulting in suppressed ZnO grain growth and deteriorated crystallinity [21]. Therefore, the deterioration in crystallinity suggests the incorporation of Al into ZnO.…”
Section: Structural Propertiesmentioning
confidence: 99%